2013
DOI: 10.1021/ja310982v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hydrogenolysis of an Iridium–Methyl Bond: Evidence for a Methane Complex Intermediate

Abstract: Evidence for key σ-complex intermediates in the hydrogenolysis of the iridium-methyl bond of (PONOP)Ir(H)(Me)(+) (1) [PONOP = 2,6-bis(di-tert-butylphosphinito)pyridine] has been obtained. The initially formed η(2)-H(2) complex, 2, was directly observed upon treatment of 1 with H(2), and evidence for reversible formation of a σ-methane complex, 5, was obtained through deuterium scrambling from η(2)-D(2) in 2-d(2) into the methyl group of 2 prior to methane loss. This sequence of reactions was modeled by density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 34 publications
3
56
0
1
Order By: Relevance
“…Collectively, these data are consistent with the identity of 3 as the Ir( iii ) complex [(C 5 H 3 N(CH 2 P( t Bu) 2 ) 2 )Ir(H 2 )(H) 2 ]BF 4 which contains a set of rapidly interchanging hydride/dihydrogen ligands. 42 It is this complex that provides the indirect route to H 2 loss that is necessary for p -H 2 introduction into 2 . We note that the related 16-electron dihydride complex [(C 5 H 3 N(CH 2 P( t Bu) 2 ) 2 )Ir(H) 2 ]PF 6 has been observed previously in the absence of CH 3 CN and found as a minimum by DFT, where it contains inequivalent hydride ligands (see Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data are consistent with the identity of 3 as the Ir( iii ) complex [(C 5 H 3 N(CH 2 P( t Bu) 2 ) 2 )Ir(H 2 )(H) 2 ]BF 4 which contains a set of rapidly interchanging hydride/dihydrogen ligands. 42 It is this complex that provides the indirect route to H 2 loss that is necessary for p -H 2 introduction into 2 . We note that the related 16-electron dihydride complex [(C 5 H 3 N(CH 2 P( t Bu) 2 ) 2 )Ir(H) 2 ]PF 6 has been observed previously in the absence of CH 3 CN and found as a minimum by DFT, where it contains inequivalent hydride ligands (see Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogenolysis mechanism of a pincer Ir III −CH 3 complex was analyzed in detail by Brookhart and co‐workers (Scheme a). Spectroscopic studies and DFT calculations revealed that reductive elimination of methane proceeds through a σ‐metathesis or σ‐CAM mechanism, in which the oxidation state of iridium is unaltered over the course of the transformation and in which a σ‐methane complex 3.18 b is an instrumental intermediate . The metal–ligand cooperative hydrogenolysis of a Ni−CH 3 bond in 3.19 has recently been disclosed and the role of the boryl ligand in assisting such transformations is supported by computational studies (Scheme b) …”
Section: Reactivitymentioning
confidence: 93%
“…Hydrogenolysis of an iridium methyl hydride complex with experimental energetics and activation barriers. [39] Scheme 14. Dissociation of methane from Pt(bpy)(CH 3 )] + by CID in gas phase.…”
Section: Alkane Càh S-bond Complexes In Combination With Other Sbond ...mentioning
confidence: 99%